Au service du public. Le « bon travail » ouvrier dans la restauration du CROUS - Ludivine Balland; Marie David; Fanny Vincent (La Nouvelle Revue du Travail, 2023)
Based on a direct observation survey and interviews with catering workers at a CROUS (Regional Center for University and School Works), this article shows how they come to deploy collective strategies so that their work can be carried out under good conditions and despite the strong constraints weighing on it.The workers rely on a public service ethic and deploy a certain ethos of working-class work: despite a deterioration, according to them, of the work and the products they have been using for the last ten years, doing good, doing beautiful and doing things together are at the heart of their concerns. The survey highlights the arduous of the work, the burden of hierarchies and a feeling of deterioration in working conditions. However, the article highlights the complexity of this dominated position, which is combined with a symbolic reassessment of the work carried out and the maintenance of autonomy.